Cost-effectiveness of single-dose AmBisome pre-emptive treatment for the prevention of cryptococcal meningitis in African low and middle-income countries. (13th January 2022) - Rajasingham, Radha; Nalintya, Elizabeth; Israelski, Dennis M; Meya, David B; Larson, Bruce A; Boulware, David R
Abstract: Cryptococcal antigen (CrAg) screening is recommended for patients with advanced HIV to reduce AIDS-related mortality. For asymptomatic CrAg-positive persons, fluconazole pre-emptive therapy is standard, despite a ∼25% failure rate. Single-dose liposomal amphotericin B (AmBisome) is non-inferior to standard treatment for cryptococcal meningitis. We evaluate the threshold of efficacy necessary for AmBisome + fluconazole to be cost-effective as pre-emptive therapy for CrAg-positive persons. We created a decision analytic model to evaluate CrAg screening and treatment in HIV-infected persons with CD4 < 100 cells/μL. Costs were estimated for screening, pre-emptive therapy, and hospitalization for an example low-income country (Uganda) and middle-income country (South Africa). We used a discounted price range of AmBisome® at $ 16.25 to $ 40 per 50 mg vial for both Uganda and South Africa. We estimated AmBisome efficacy from 75 to 95%. Parameter assumptions were based on prospective CrAg screening studies and clinical trials in Africa. Disability adjusted life years (DALYs) were calculated using the age-specific life expectancy in Uganda, per WHO Global Health Observatory data. We modeled the theoretical efficacy of adjunctive AmBisome to determine cost per DALY averted. In South Africa, at $ 16.25 per vial cost and a minimum efficacy of 85%, adjunctive AmBisome is cost-saving compared to fluconazole monotherapy. Compared to fluconazole pre-emptive therapy in Uganda, AmBisome + fluconazole would cost $ 475, $ 220, or $ 136 per DALY averted if meningitis-free survival efficacy was 80, 85, or 90% at $ 24 per vial cost. Investing in AmBisome may be cost-effective in low-income settings compared to using fluconazole pre-emptive therapy alone, if efficacy is 85% or greater. AmBisome pre-emptive therapy appears more cost-efficient in middle-income settings where hospitalization costs for meningitis, and GDP per capita are higher. Lay Summary: We evaluate the efficacy necessary for AmBisome + fluconazole to be cost-effective to prevent cryptococcal meningitis. We found that if AmBisome pre-emptive therapy has an efficacy of 85% or greater, it is likely to be cost-effective in low-income settings.